Outliers: The Story of Success - Malcolm Gladwell (USA Back Bay Books, 2011)
In this stunning book, Malcolm Gladwell takes us on an intellectual journey through the world of "outliers"--the best and the brightest, the most famous and the most successful. He asks the question: what makes high-achievers different? His answer is that we pay too much attention to what successful people are like, and too little attention to where they are from: that is, their culture, their family, their generation, and the idiosyncratic experiences of their upbringing. Along the way he explains the secrets of software billionaires, what it takes to be a great soccer player, why Asians are good at math, and what made the Beatles the greatest rock band. Brilliant and entertaining, Outliers is a landmark work that will simultaneously delight and illuminate.
Keywords: Nonfiction; Psychology; Sociology; Self Help; Business